The Attitude of the Regional Editors of Lithuanian Periodicals to the Principles of Distribution of State Support for the Media - Kėvišas, Magnus Tomas; Brazauskas, Arūnas; Nedzveckienė, Violeta; Myštautaitė, Milda (Žurnalistikos tyrimai, 2021)
It is often maintained that there is no one consistent mass media policy in Lithuania. There are, indeed, many mechanisms of state financial aid and support, and the allocation of funds itself is rather inconsistent and accidental. There is no data or information available as to how the strengths and weaknesses of the particular mechanisms created and aid/funding opportunities available are perceived by the target audience of such efforts – the staff of the editorial boards of the news outlets and the particular business owners. Having conducted a questionaire-based study and a series of in-depth structured interviews with selected typical representatives from the industry, here we delineate the perception: the editorial staff maintain that the most impactful mechanism of allocating state support for the press are direct payments, especially those distributed by the Lithuanian Media Support Foundation, though the principles regulating its decision-making should be amended so as to allow for more transparency. One should also ensure that whatever is being funded has a case for continuity, sustainability and long-term future in regard to its activities. Additionally, especially inasmuch as any allocation of funds is related to an attempt to ensure the long-term success of democratic governance, the funding is to be targeted at local news rather than national or international news. These findings are shown to be comparable to tendencies observed abroad.
Keywords: media policy; state support for the media; regional periodicals; regional editions